1992
DOI: 10.1530/acta.0.1270220
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of tumor necrosis factor-α on human thyroid follicular cells

Abstract: Tumor necrosis factor-α is assumed to be an important mediator in thyroid autoimmunity. In the present study we have shown that human thyrocytes possess a single specific binding site for recombinant tumor necrosis factor-α with an average of 9,300 receptors/cell (Kd = 1.9 · 10−10 mol). The effects of the cytokine on thyroid cell proliferation were assessed by 3H-thymidine uptake as well as by the protein and DNA content of cell monolayers. Low dose tumor necrosis factor-α resulted in a moderate stimulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Human thyrocytes possess a specific receptor for TNF- [1]. TNF-has been suggested as a possible mediator of increased expression of MHC class I molecules on thyroid epithelial cells in GD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human thyrocytes possess a specific receptor for TNF- [1]. TNF-has been suggested as a possible mediator of increased expression of MHC class I molecules on thyroid epithelial cells in GD.…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of this cytokine in the pathogenesis of autoimmune thyroid diseases is still unclear. TNF-receptors have been shown on thyroid epithelial cells and FRTL-5 cells, and a multitude of TNF-in vitro actions have been demonstrated on these cells [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Their assay system differed from ours in that they used pretreatment with IFN-for 5 days followed by a shortterm (120 min) incubation with TSH. In the study of Kraiem et al (1990), as well as in that of Deuss et al (1992), the augmentation of the acute TSH-induced cAMP production could have been caused by an altered sensitivity of the cells to TSH caused by increased activity of the TSH receptor/adenylate-cyclase system following inhibition of the metabolic pathways induced by longterm exposure to IFN-or TNF-. In contrast, our study describes the simultaneous effects of TSH and the cyto¬ kines.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, low level cytokine production by thyrocytes can directly stimulate, in a paracrine or autocrine fashion, the growth of thyroid cells (18,19) via the secretion of Il1␣ (20), Il6 (21), or IL4 and IL10 (17). Moreover, previous work has demonstrated that RET/PTC3 (RP3) can directly induce the production of these and other inflammatory factors (12) and, when such cells are transplanted into mice, induce the attraction of activated macrophages.…”
mentioning
confidence: 99%